DAMPAK PENGEMBANGAN DESA WISATA TERHADAP EKONOMI SOSIAL MASYARAKAT DESA KARANGSALAM KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Muhammad Syafiq Thobari; Shindu Bayu Wisanggeni; Siti Maghfiroh; Widia Eka Restiani; Wulan Linda Puspita Sari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
A promising trend to improve the economy and welfare of the population in rural areas is the development of tourist villages. Karangsalam Village, located in Baturraden District, Banyumas Regency, is one example of a village that has succeeded in taking advantage of its tourism potential. This study looks at how the development of tourist villages has an impact on the economy and local communities of Karangsalam Village. The focus of this research is on changes in income and community welfare. Field observation, community interviews, and literature research are the methods used to conduct this research. According to the results of the study, creating a tourist village in Karangsalam village will increase the income and welfare of the community. The increase in the number of tourists has driven the growth of many new businesses, such as homestays, cooking, and handicrafts, which provide additional job opportunities for the community.